2017
DOI: 10.1093/mnras/stx798
|View full text |Cite
|
Sign up to set email alerts
|

Transit probabilities in secularly evolving planetary systems

Abstract: This paper considers whether the population of known transiting exoplanets provides evidence for additional outer planets on inclined orbits, due to the perturbing effect of such planets on the orbits of inner planets. As such, we develop a semi-analytical method for calculating the probability that two mutually inclined planets are observed to transit. We subsequently derive a simplified analytical form to describe how the mutual inclination between two planets evolves due to secular interactions with a wide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…If the orbit of Kepler-129 d is inclined with respect to those of the inner planets, it could have imposed a torque on the inners and excited them out of the equatorial plane of the host star. In addition to exciting the spin-orbit angle, an inclined outer giant planet could also excite mutual inclinations between inner planets, possibly preventing them from transiting together (Becker & Adams 2017;Lai & Pu 2017;Read et al 2017). The fact that we observe both Kepler-129 b and c to be transiting places an additional constraint on the inclination of Kepler-129 d. In other words, the inclination of d must be large enough that a spin-orbit angle of ∼38°can be produced, while small enough that both planets b and c have a large probability of transiting together.…”
Section: Orbital Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the orbit of Kepler-129 d is inclined with respect to those of the inner planets, it could have imposed a torque on the inners and excited them out of the equatorial plane of the host star. In addition to exciting the spin-orbit angle, an inclined outer giant planet could also excite mutual inclinations between inner planets, possibly preventing them from transiting together (Becker & Adams 2017;Lai & Pu 2017;Read et al 2017). The fact that we observe both Kepler-129 b and c to be transiting places an additional constraint on the inclination of Kepler-129 d. In other words, the inclination of d must be large enough that a spin-orbit angle of ∼38°can be produced, while small enough that both planets b and c have a large probability of transiting together.…”
Section: Orbital Dynamicsmentioning
confidence: 99%
“…In order to quantify whether the simulated inner planets transit together as observed, we define the parameter doubletransit pprobability (DTP) for Kepler-129 b and c (e.g., Becker & Adams 2017; Read et al 2017). DTP is the fraction of time when two inner planets can both be observed to transit from any line of sight along their mutual ecliptic.…”
Section: Double-transit Probabilitymentioning
confidence: 99%
“…Nevertheless, the detection of wide orbit giant planets can place stringent constraints on the architecture of the inner planets (e.g. Becker & Adams 2016;Read & Wyatt 2016;Mustill et al 2016;Hansen 2017;Lai & Pu 2017;Read et al 2017), and the existence of unseen planets invoked to explain structure observed in debris belts (e.g. β Pic Lagrange et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They also point out, however, that dynamical evolution due to the outer planets alone is insufficient to explain the excess of Kepler 's single-transit systems. Read et al (2017) also suggest that single-transit systems may have inclined/non-transiting outer planets. On the other hand, a recent study by Izidoro et al (2017) suggests that when the gas disk is present, planetary embryos grow and migrate inward.…”
Section: Introductionmentioning
confidence: 98%